The Cytokine Profiles and Immune Response Are Increased in COVID-19 Patients with Type 2 Diabetes Mellitus - Mao Zheng; Xiaobing Wang; Hui Guo; Yinguang Fan; Zichen Song; Zhaohui Lu; Jinquan Wang; Changcheng Zheng; Lin Dong; Yan Ma; Yuyou Zhu; Haoshu Fang; et al. (Journal of Diabetes Research)
The induction of inflammation and cytokine storm was proposed to play a critical role in COVID-19. This study is aimed at investigating the relationship between glucose metabolism and the inflammatory state of inpatients with COVID-19. 71 inpatients with COVID-19 were classified into nondiabetes mellitus (NDM) group, impaired fasting glucose (IFG) group, and diabetes mellitus (DM) group. The average hospitalization days were significantly shorter in DM patients when compared with patients in the IFG group and NDM group. CD4+ T cell percentage was higher while CD8+ T cells percentage was lower in the DM group than those in the NDM group. The serum levels of IL-6, IL-2, IL-10, and INF-γ in the DM group were upregulated when compared with those in the NDM group. The serum levels of TNF-α, IL-4, IL-2, IL-10, and INF-γ were significantly higher in the DM group than those in the IFG group. A significant difference was observed in CD4+ T cell, CD4+/CD8+ ratio percentage, IL-6, and IL-10 between the NDM group and DM group with adjusted BMI. In conclusion, COVID-19 patients with elevated glucose levels have promoted cytokine profiles and immune response.